Sharing Mining Benefits in Developing Countries - Wall, Elizabeth; Pelon, Remi (World Bank, Washington, DC, 2014)
This publication examines the role of foundations, trusts, and funds (FTFs) in delivering benefits derived from mining projects in the developing world. Chapter two addresses the necessity of sharing benefits from mining projects and identifies the situations under which a dedicated instrument such as an FTF can support that process. Chapter three reveals both the diversity and similarities of FTFs by reviewing six key attributes: their programming approach; their financing structure; their geographic focus; the extent of community participation in governance; the influence of the mining company on FTF operations; and the influence of the government on the FTF. Chapter four identifies key conditions for success and areas of leading practice based on experience with mining FTFs globally and drawing on specific cases in Namibia, Papua New Guinea, Peru, and South Africa.